1994
DOI: 10.1017/s0007123400006785
|View full text |Cite
|
Sign up to set email alerts
|

Partisan Dealignment and the Dynamics of Independence in the American Electorate, 1953–88

Abstract: Since the 1950s, the dominant pattern of partisan change in the American electorate has involved movements between party identification and independence rather than direct or indirect shifts between parties. This article employs switching regression analyses to investigate the long-term evolution and short-term dynamics of independence between 1953 and 1988. The analyses reveal that a new ‘independence regime’ developed rapidly in the mid-1960s, with the ‘tipping point’ in the transition occurring in the secon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0
1

Year Published

1994
1994
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(17 citation statements)
references
References 31 publications
0
16
0
1
Order By: Relevance
“…Despite this scientific effort, our knowledge about the individual level dynamics of party identification is limited at best. While recent research has made some progress on the methodological front, we argue that a key ingredient of a potent model of partisan dynamics is its bounded nature (Clarke and Suzuki 1994;Zuckerman and Kroh 2006;Zuckerman et al 2007). This implies that there is no 'party menu' from which individuals choose freely every time they are surveyed.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…Despite this scientific effort, our knowledge about the individual level dynamics of party identification is limited at best. While recent research has made some progress on the methodological front, we argue that a key ingredient of a potent model of partisan dynamics is its bounded nature (Clarke and Suzuki 1994;Zuckerman and Kroh 2006;Zuckerman et al 2007). This implies that there is no 'party menu' from which individuals choose freely every time they are surveyed.…”
Section: Introductionmentioning
confidence: 89%
“…Decisions concerning the construction of party identification variables often make the implicit assumption that voters select one from all of the available parties, but empirical evidence supplied by election study panels in America and elsewhere suggest that voters engage in a restricted search when choosing a party to support. Clarke and Suzuki (1994) and Clarke and McCutcheon (2009) establish that most of the switching is from identification with one party to non-identification (or independence) or vice versa and not across parties. Furthermore, they find that those who switch from supporting a major party to independence are not just using their new found non-identification as a half-way house en route to forming an identity or supporting another party.…”
Section: Bounded Partisanship and The Question Of Individual Changementioning
confidence: 99%
“…Elections are a constant, not a variable, feature of the context in which surveys such as the ANES and BES are held. The possible implications of this are suggested by Clarke and Suzuki's (1994) multivanate analysis of the US Gallup party identification data. They find that the percentage of nonidentifiers ('independents') declines significantly when presidential and off-year congressional elections are held, but rebounds thereafter.…”
Section: Aggregate-level Dynamicsmentioning
confidence: 99%
“…There are reasons to believe that Wallas might not reach this conclusion today. Voters' psychological attachments to parties, as measured by responses to standard questions on party identification, appear to have weakened appreciably in countries such as Great Britain and the United States since the first major national election surveys were conducted several decades ago (Clarke and Stewart, 1984;Clarke and Suzuki, 1994;Sarlvik and Crewe, 1983;Wattenberg, 1994). The same can be said about the evolution of partisan attachments in a variety of other mature democracies (e.g., Clarke and Kornberg, 2000: ch.…”
mentioning
confidence: 99%
“…Previous studies have identified short-term fluctuations in political independence linked to issue preferences, economic conditions, socialization, and periodic political events such as campaigns and elections (Clarke and Suzuki, 1994;Clarke and Stewart, 1998;Greene, 2002;MacKuen et al, 1989;Niemi et al, 1991;Sears and Valentino, 1997). Weakening party ties leads to an increase in the instability of voter preferences over time (MacKuen et al, 1989;MacKuen et al, 1992), a trend that corresponds to an increase in the number of swing voters and swing states and perhaps indicates the decline of partisanship in the U.S. and Britain (Clarke and Stewart, 1998;Clarke and Suzuki, 1994;Fiorina et al, 2005;Mayer, 2007). These studies taken together suggest that, one's national identification can be as stable as party identification.…”
Section: Introductionmentioning
confidence: 99%